A Glimpse into the Future of the Climate Regime: Lessons from the REDD+ Architecture. Issue 2 (July 2016) - Savaresi, Annalisa
Abstract : In 2015, parties to the United Nations Framework Convention on Climate Change (UNFCCC) formally closed negotiations on measures to maintain and enhance the carbon storage capacity of forests in developing countries, commonly referred to as 'REDD+'. This unusual and largely symbolic gesture seemingly signals that UNFCCC parties consider the international set of rules on REDD+ a 'job done', at least for the time being. This article reflects on the outcome of these negotiations and on the related lawmaking process, arguing that REDD+ may be regarded as the first ripe fruit in the pledge‐and‐review architecture recently enshrined in the Paris Agreement. REDD+ is therefore used in this article as a lens to understand how the new architecture for climate change governance may work, as well as challenges facing its implementation. In doing so, the article aims to shine a light on the path ahead for the Paris Agreement, making predictions on challenges likely to emerge with its implementation, the solutions that may be adopted, as well as areas where more international rules may be needed.